Influence of heterogeneity, natural fracture, and bedding plane on fracture propagation in the vicinity of a borehole. Issue 3 (October 2021) - Zhang, Pei; Ma, Tianshou; Liu, Yang
Abstract: The majority of lost circulation events during drilling include drilling fluid losses through natural or drilling-induced fractures, but this problem can be prevented by understanding fracture propagation behavior. However, studies have mostly focused on the influence of natural fracture and bedding planes on hydraulic fracture propagation, and few studies have explored the fracture propagation in the vicinity of a borehole. Therefore, the present paper intends to simulate the fracture propagation in the vicinity of a borehole under the joint impact of heterogeneity, natural fracture, bedding planes, and borehole. The theoretical model of flow-rock failure process analysis 2D was introduced, and the uniaxial compressive testing results of Longmaxi shale were obtained to verify the present model. Then, fracture propagation models in the vicinity of a borehole were proposed by considering heterogeneity, bedding planes, and natural fracture. Numerical findings were analyzed and discussed. Results indicated that heterogeneity, bedding planes, and natural fracture significantly influenced fracture propagation in the vicinity of the borehole. As such, this influence should be considered in the analysis and treatment of lost circulation. This study could help elucidate how lost circulation could be prevented during drilling in fractured formations.